1994
DOI: 10.1007/978-94-011-1050-1_13
|View full text |Cite
|
Sign up to set email alerts
|

Detonation Waves and Propulsion

Abstract: The possibility of using a detonation wave as the key combustion system for supersonic propulsion is examined. A brief review of propagating detonations is provided first. This review emphasizes the unique and unstable nature of the coupling between reaction zone and shock waves that characterize detonations. The theory of idealized, steady, oblique detonation waves and their reaction zone structure are summarized. The evidence for the existence of stabilized or steady oblique detonations is discussed. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…revealed that the flow field is steady and simply translating along the cord length. The existence and stability of CJ oblique detonations is thus confirmed (Pratt et al 1991;Shepherd 1994).…”
Section: Direct Initiation Of Detonation In Combustible Gasmentioning
confidence: 70%
See 1 more Smart Citation
“…revealed that the flow field is steady and simply translating along the cord length. The existence and stability of CJ oblique detonations is thus confirmed (Pratt et al 1991;Shepherd 1994).…”
Section: Direct Initiation Of Detonation In Combustible Gasmentioning
confidence: 70%
“…In this sense, the ability to predict the critical energy for the direct initiation of a cylindrical detonation provides a first-order estimate on the critical conditions for detonation initiation by a hypervelocity projectile. Furthermore, the stability of the resulting oblique detonation initiated around a projectile is of significance to applications that seek to stabilize oblique detonation waves in propulsion applications (Pratt, Humphrey & Glenn 1991;Shepherd 1994). To date, the limited velocities of gas-gun-launched projectiles, which are of the order of the Chapman-Jouguet (CJ) detonation velocity (≈ 2 km s −1 ), has not permitted observation of steady oblique detonation waves.…”
Section: Introductionmentioning
confidence: 99%
“…By assuming a stationary one-dimensional situation consisting of a shock and a succeeding reaction, the governing equations can be transformed into a system of ordinary differential equations depending only on the distance behind the shock front. Detailed accounts of the elaborate derivation can be found for instance in [16,19,18].…”
Section: Governing Equationsmentioning
confidence: 99%
“…doi:10.1016/j.jcp.2006. 10.006 in aerospace science mainly being a promising combustion mechanism for hypersonic propulsion devices such as pulse detonation engine, oblique detonation wave engine, and ram accelerator [3].…”
Section: Introductionmentioning
confidence: 99%